1994
DOI: 10.1097/00006842-199401000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adrenergic receptors and adrenergic agonists underlying cardiovascular responses to a psychological challenge.

Abstract: Numerous physiological and biochemical factors contribute to the dynamic regulation of the cardiovascular system. This study used a cluster analytic statistical technique to discern patterns of adrenergic receptors and adrenergic agonists underlying cardiovascular responses to a laboratory challenge. Fifty hypertensive and normotensive black and white individuals had their beta- and alpha-adrenergic receptor sensitivity determined through agonist infusions. Norepinephrine, epinephrine, blood pressure, and hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
(39 reference statements)
2
14
0
Order By: Relevance
“…It is possible that the disordered eating behaviour is associated with diminished badrenergic activation. Alternatively, individuals vary in the sensitivity of b adrenergic receptors (Mills et al, 1994), and it is also possible that disordered eating is association with reduced receptor sensitivity. There is at least some evidence in favour of the former as bulimics have been found to show blunted norepinephrine reactions to stress (Pirke et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the disordered eating behaviour is associated with diminished badrenergic activation. Alternatively, individuals vary in the sensitivity of b adrenergic receptors (Mills et al, 1994), and it is also possible that disordered eating is association with reduced receptor sensitivity. There is at least some evidence in favour of the former as bulimics have been found to show blunted norepinephrine reactions to stress (Pirke et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Density of beta adrenergic receptors accounted for more of the response variance than traditional response measures, such as catecholamine activation, and these traditional measures in conjunction with receptor densities accounted for a considerable amount of the response variance. Cluster analysis of results from a large group of individuals indicated that peripheral receptor compliments may be a dominant factor in determining reactions to mental stress (Mills et al, 1994). An implication of these findings is that descending influences reflecting activation at the level of the frontallimbic system or at the hypothalamus and brainstem will nonetheless have greater influences on persons with greater numbers of peripheral adrenergic receptors.…”
Section: Cardiovascular Activity In Men At High Riskmentioning
confidence: 95%
“…Although catecholamine reactivity testing would be desirable, subject blood draw burdens (testing requires placement of an indwelling catheter) and substantial laboratory burdens for these particular tests precluded inclusion of such measures [84][85][86].…”
Section: Cardiovascular Reactivity Testmentioning
confidence: 99%